Effect of Acidified Drinking Water on the Recovery of Salmonella enteritidis from Broiler Crops - LAF de Avila (Revista Brasileira de Ciência Avícola, 2003)
Crop is a known source of Salmonella contamination during broiler carcass processing. The effect of drinking water acidification by lactic acid or citric acid or a combination of those with cupric sulfate and d-limonene in the reduction of Salmonella Enteritidis (SE) recovered from the crop of broilers was evaluated. Treatments were administered during 8 hours of preslaughter fasting period (Experiments I and II) and during the last 32 hours of preslaughter (Experiment III). It was observed that acidification reduced water intake when treatments began at preslaughter feed withdrawal, and affected the possible reducing effect of these acids on SE recovering (Experiments I and II). Water intake during preslaughter feed withdrawal was not affected when treatment began 32 hours before slaughter (Experiment III). Treatments reduced SE recovering from crop (p<0.05). In Experiment III, 0.470% of lactic acid reduced the number of recovered SE in 99%. This study suggested that the addition of organic acids in the drinking water 24 hours before beginning the preslaughter feed withdrawal might reduce crop SE colonization and might be an important strategy to reduce SE contamination of broiler products during processing.